Relationship of chip load and spindle speed on cutting force and surface integrity for high-speed dry end-milling Hastelloy X material - Mohd Nor, Nor Aznan (2019)
The effect of the cutting force during high-speed machining (HSM) has been extensively focused on by many researchers and the existing literature mainly discuss the approaches that can be taken to reduce the cutting force when machining nickel-based superalloys, such as by reducing the chip load while increasing the spindle speed. Increasing the spindle speed can increase the cutting speed, which indirectly reduces the cutting force. While, a reduction in the chip load decreases the cutting force needed to remove the unwanted material. On the other hand, a decrease in chip load results in low material removal rate (MRR). Therefore, it is contrary to the principle of HSM, where increasing the spindle speed while reducing the chip load only reduce the cutting force, rather than reducing the cutting force and increasing the MRR. Furthermore, it has been proven that the surface integrity after machining directly affects the reliability and life of the product. Although the ultimate research goal of the cutting force is to improve cost-effectiveness and productivity, it is also crucial to maintain or improve the surface integrity of a product. Therefore, the main aim of this research is to study the influence of increases in spindle speed at constant chip load on the cutting force and surface integrity of high-speed end-milling of Hastelloy X material under dry conditions. The cutting force behaviour was simulated by using AdvantEdge, while dynamometer was used to measure the cutting force under experimental tests. The research then analysed the surface integrity of Hastelloy X. Surface integrity, that included surface roughness, surface hardness and sub-surface residual stress, was observed with the purpose of correlating it with the optimum combination of chip load and spindle speed under experimental conditions, and also the behaviour of cutting force components and resultant force. Results of the experimental tests revealed that the cutting force components and resultant force had quadratic behaviour. In addition, axial force was the dominant factor affecting the resultant force, followed by the normal force and feed force. In terms of surface integrity, the surface roughness and sub-surface residual stress were in line with the behaviour of the cutting force components and resultant force. However, the behaviour of surface hardness did not necessarily correspond to the behaviour of the cutting force components and resultant force when the spindle speed was increased at a constant chip load. Finally, the ideal combination of chip load and spindle speed in order for the manufacturing industry to obtain the ideal cutting force, MRR and surface integrity during high-speed end-milling of Hastelloy X under dry conditions at 0.2 mm depth of cut was proposed at 0.016 mm/tooth and 21,400 rpm in half-immersion down-milling, 0.019 mm/tooth and 23,920 rpm in half-immersion up-milling, 0.016 mm/tooth and 23,560 rpm in full-immersion down-milling, and 0.016 mm/tooth and 24,640 rpm in full-immersion up-milling.